Canvas LMS course design : design, build, and teach your very own online course using the powerful tools of the Canvas Learning Management System - John, Ryan (Community experience distilled., 2014)
This book is intended for educators who want to use Canvas to enhance their teaching or for educators whose institution has adopted Canvas as its learning management system. Whether you are brand new to online learning or you are a seasoned expert, you will be able to master both the basic functions and the advanced features of Canvas with this book.